2017
DOI: 10.1111/neup.12411
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes‐associated neurosarcoidosis: A case report with review of the literature

Abstract: A 56-year-old woman with a 3-year history of hydrocephalus and ventriculo-peritoneal shunt placement, presented with worsening altered level of consciousness for 2 days. Imaging studies showed severe ventriculomegaly involving the lateral and third ventricles with multiple septated cysts noted in the lateral ventricles predominantly near the frontal horns. Histopathologic examination of the excised brain lesion revealed choroid plexus tissue and adjacent cerebral parenchyma with several non-caseating granuloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Yang et al reported a case of P. acnes-associated neurosarcoidosis identified by immunohistochemical analysis of the brain tissue using PAB antibody [25]. Contrarily, our case differs from sarcoidosis because pathological analyses did not reveal the presence of noncaseating granulomas.…”
Section: Discussionmentioning
confidence: 63%
“…Yang et al reported a case of P. acnes-associated neurosarcoidosis identified by immunohistochemical analysis of the brain tissue using PAB antibody [25]. Contrarily, our case differs from sarcoidosis because pathological analyses did not reveal the presence of noncaseating granulomas.…”
Section: Discussionmentioning
confidence: 63%
“…Yang et al reported a case of P. acnes-associated neurosarcoidosis identified by immunohistochemical analysis of the brain tissue using PAB antibody [25]. Contrarily, our case differs from sarcoidosis because pathological analyses did not reveal the presence of non-caseating granulomas.…”
Section: Discussionmentioning
confidence: 64%
“…Broad-spectrum anti-mycobacterial therapy has demonstrated positive effects on lung function in chronic sarcoidosis patients [46], although this was primarily attributed to anti-inflammatory effects rather than specific pathogen eradication [47]. In addition, P. acnes has been associated particularly with certain manifestations of sarcoidosis such as ocular, cardiac and neurological involvement [48][49][50][51], and more recent studies show alterations in the pulmonary microbiome in sarcoid compared to healthy lungs [52]. However, as presence of bacterial DNA [53] and protein [5] have been reported in ∼50% of investigated sarcoidosis patients, and as live mycobacteria have never been identified in or cultured from sarcoid lungs, these findings cannot account for all patients.…”
Section: Sarcoidosis Results From Immune Hyperactivitymentioning
confidence: 99%